All the bright places - Niven, Jennifer (New York : Alfred A. Knopf, 2015)
"Told in alternating voices, when Theodore Finch and Violet Markey meet on the ledge of the bell tower at school--both teetering on the edge--it's the beginning of an unlikely relationship, a journey to discover the "natural wonders" of the state of Indiana, and two teens' desperate desire to heal and save one another"
Includes bibliographical references.
Keywords: Friendship -- Fiction; Suicide -- Fiction; Emotional problems -- Fiction; Indiana -- Fiction